Migraciones y teatro: conformación de un nuevo mapa teatral cubano, más allá de la insularidad palpable - Ileana Azor (Les Cahiers ALHIM)
Cuban migration to Europe and America (North, Central and South) has designed a creative and pedagogical map that expands its original theatrical geography into the new “lived spaces” (Ortiz & Mendoza) -sometimes these being bilingual spaces. In the last fifty years Cuban migrants have processed their journeys of displacement by recovering their own cultural History through the generation of new Imaginaries and Institutions, creating in consequence new aesthetic scenarios articulated by a “frontal discourse” or a “rhetorical tissue” (Azor). These new aesthetic scenarios reveal the multicultural dialogue of a transcending “cubanidad”.